Day-to-day variability of post-concussion-like symptoms reported over time by a non-concussed cohort. (5th December 2016) - Balasundaram, Arun Prasad; Athens, Josie; Schneiders, Anthony G.; McCrory, Paul; Sullivan, S. John
Abstract: Primary objective : To explore the change (trend) in post-concussion-like symptoms reported over time. Research design : Longitudinal study. Methods and procedures : University students aged 18–30 years self-reported their symptoms experienced on a daily basis. Each participant was contacted via a text message each day during one of three pre-defined time zones to complete the Sport Concussion Assessment Tool 2 (SCAT2) post-concussion symptom scale on 7 consecutive days. Main outcomes and results : One hundred and ten (26 males and 84 females) students completed the study on all 7 days. Only two meaningful clusters emerged and comprised of a total of 105 participants. The primary cluster included 85 participants who showed a relatively stable pattern in their symptoms reported over time. Meanwhile, a second cluster comprised of 20 participants who demonstrated a decreasing trend in the reported symptom scores. Conclusions : The data indicated that non-concussed participants exhibited considerable individual variability in the symptom scores reported over time. However, some participants showed a systematic decreasing trend in their symptom scores reported over the 7 days. Caution must be exercised in interpreting the serial symptom scores that are obtained following a concussion, given that this study was conducted in a non-concussed cohort.